MODEL PEMBELAJARAN TEMPE KEMUL (TEMUKAN, PERMAINAN, KESIMPULAN, MULAI LAKUKAN) MENGGUNAKAN PENDEKATAN TPACK UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN PKN KELAS VI SD N BUMIRESO - Sri Haryati Rahayuningsih; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted using qualitative methods and a grounded theory approach, involving a teacher and 24 sixth grade students as research subjects. The research instruments used were observation notes and unstructured interviews. Before implementing the Tempe Kemul Learning Model using TPACK, students already had knowledge of ICT but digital innovation and creativity were not yet visible. After implementing the Tempe Kemul Learning Model using TPACK, 15 out of 24 students showed the development of digital innovation and creativity. The Tempe Kemul Learning Model using TPACK not only improves student learning outcomes in cognitive and affective aspects, but also stimulates students' digital innovation and creativity through PjBL-based projects. Thus, this learning model can be used as an effective alternative in improving the quality of PKN learning by integrating the Tempe Kemul learning model using TPACK, differentiated learning, and the TPACK approach.